Value in capitalist society : rethinking Marx's criticism of capitalism - Cobben, Paul. (Critical Studies in German Idealism, 2015)
Marx's analysis of the commodity results in his conception of Capital as substance in the form of alienation. While Hegel claims that substance can be understood as the realization of freedom, Marx shows this freedom to be alienated labor: abstract labor, which Marx identifies as the capitalist conception of value. The book clarifies why Marx's so-called materialist criticism of Hegel can be conceived of as an immanent criticism of Hegel: Marx's criticism explicates that the realization of freedom in the Philosophy of Right contradicts Hegel's basic point of departure. The adequate realization of freedom not only leads to an alternative (non-alienated) conception of value, but also explains why this conception of value is fully compatible with the free market.